Strawberries decrease circulating levels of tumor necrosis factor and lipid peroxides in obese adults with knee osteoarthritis. Issue 12 (1st November 2018) - Basu, Arpita; Kurien, Biji T.; Tran, Huyen; Byrd, Bre'Ana; Maher, Joey; Schell, Jace; Masek, Emily; Barrett, James R.; Lyons, Timothy J.; Betts, Nancy M.; Hal Scofield, R.
Abstract : Objective : Knee osteoarthritis (OA) is increasingly prevalent in obese people, who often have high cardio-metabolic risk factors. We examined effects of strawberries on knee OA. Abstract : Objective : Knee osteoarthritis (OA) is increasingly prevalent in obese people, who often have high cardio-metabolic risk factors. Among the few available non-surgical approaches, nutraceuticals have gained popularity, and dietary berries have mitigated arthritis symptoms in observational and animal studies. Clinical studies in OA are sparse, but recently we reported that strawberry supplementation can mitigate pain and reduce inflammatory markers in adults with knee OA. This study extends those observations. Methods : We conducted a randomized cross-over double-blind placebo-controlled trial on the effects of dietary freeze-dried strawberries on obesity-related hormones, biomarkers of inflammation and lipid peroxidation. Seventeen subjects (4 men, 13 women; age 57 ± 3 year) were randomized to strawberry supplements (50 g day −1 for 12 weeks) vs. placebo (50 g day −1, matched for calories and fiber), for two 12-week intervention periods, separated by 2-week washout phase. Results : Among 24 biomarkers of inflammation examined (Bioplex-Pro human inflammation panel), 12 were detectable in all samples. Among these, high-sensitivity TNF-α (hs-TNF-α) and the soluble tumor necrosis factor receptor (sTNF-R2) were significantly decreased after strawberry consumption ( p < 0.05). There were no changes in other biomarkers of the TNF super family, such as APRIL and BAFF. Among serum biomarkers of oxidative stress, 4-hydroxy-2-nonenal (4-HNE) and conjugated dienes were also reduced ( p < 0.05). No changes were observed in body weight, serum obesity-related hormones, or osteocalcin. Conclusion : Strawberries lowered TNF-α, and lipid peroxidation products in obese adults with knee OA. Since, they also mitigate pain, these findings merit further investigation in larger trials.